Radiophysical methods for solving problems of non-destructive testing and remote sensing in the frequency domain - Батраков, Д. О. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 2019)
The review is devoted to the current state of solving inverse scattering problems in the frequency domain. The analysis of methods and various approaches to solving inverse scattering problems allowed us to more deeply understand the fundamentals of physical and mathematical models and algorithms of processing recorded experimental data sets. From the point of view of the computational methods development, the conducted numerical experiments showed the high efficiency of the proposed methods and algorithms and made it possible to suggest ways of further improvement not only of the mathematical apparatus and corresponding methods and algorithms but also ways of further development and improvement of sensing tools. This primarily relates to the requirements for antennas and, as a result, to the form and parameters of the sensing pulses. In this case, the obtained results are designed to ensure the solution of important practical problems and will contribute to the further development of the theoretical foundations of processing and interpreting the observed data in the case of electrodynamically complex structures sensing.